IMPLEMENTASI STEGANOGRAFI UNTUK MENYISIPKAN PESAN TEKS PADA MEDIA GAMBAR DENGAN METODE END OF FILE - Wamiliana Wamiliana; Astria Hijriani; Azharico Darusman (Universitas Lampung, 2015)
Security and confidentiality of data transmission are two important aspects in the era of openness to data access and information. One way to secure the data transmission is using steganography. In this research, the method used is End Of File (EOF) and used image as the medium. The message is hidden by inserting it in the end of the line image file. The media for hiding the message is in the form of .jpg and the output is in the form of .png. Inputting message is done manually. Testing have been conducted on 5 types of images with different resolutions with a number of different messages characters which are 10, 100, and 1000 characters. The results show that the method of End Of File (EOF) successfully used to hide message in the media image and to take back the message that has been inserted. The image size and the number of characters used affects the processing time for embedding and extracting. Cropping, contrasting, and brightness on stego image are conducted to analyze the resilience of the message inserted. The results show that the stego image manipulations are sensitive or resistant to the manipulation that makes the message becomes corrupted and are not recommended in manipulating stego image.Keywords : embed, End Of File (EOF), extract, image, steganography, stego Image